Response Surface Optimization of Ultrasonic-Assisted Oil-Conjugated Reaction Using Solid Nickel Catalyst - Ri-Fu, Yang; Qi-Qi, Deng; Jie, Yan (Asian Journal of Chemistry, 2013)
The effect of ultrasonic irradiation on oil-conjugated reaction using solid catalyst has been investigated. Through single factor tests and response surface methodology (RSM), batch processes assisted with 20 kHz ultrasound were performed to study the impacts of ultrasonic power, temperature, catalyst loading and reaction time on the content of conjugated linoleic acid. The multivariate analysis results indicated that the optimum reaction conditions were ultrasonic power of 240 W, temperature of 180 ºC, catalyst loading of 8 wt. % and reaction time of 1 h, at which the highest product yield of 4.644 mg/mL was achieved. Reaction time was found to exert the most significant weight on the variability of the conjugated linoleic acid concentration, followed by system temperature. In the present research, the resultant content under ultrasonic cavitation realized an adequate raise, compared with the conventional magnetic stirring reactor.